MODEL PENGELOLAAN ALOKASI DANA DESA DI KABUPATEN MERANTI - Irwan Nasir; Agus Maulana (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2021)
The purpose of this study is to find out more about the allocation of village fund management by village/sub organizations that are directly involved in the aspects of Strategic Leadership and Officer Commitment in carrying out distribution and implementation according to the Musrenbangdes and see government policy gaps in flexibility and maximizing the use and management of village fund allocations to encourage the creation of Budget performance in development and priorities according to the agreement with the community according to the vision, mission and objectives of village development in the Meranti Islands Regency with a quantitative method as many as 309 respondents. The results of the study show that there is still a need for Knowledge Management for organizational members, Agile Management in dealing with environmental changes and the urgency of the current situation, as well as increasing knowledge in budget implementation regulations and skills for members to motivate stakeholders the Village Fund allocation budget in increasing the budget in the coming year. Tujuan penelitian ini ingin mengetahui lebih dalam alokasi pengelolaan dana desa oleh organisasi desa/kelurahan yang terlibat langsung dalam aspek Kepemimpinan Strategis dan Komitment Petugas dalam melaksanakan pendistribusi dan pelaksanaan sesuai Musrenbangdes dan melihat celah Kebijakan Pemerintah dalam flexibility dan maksimalisasi penggunaan dan pengelolaan alokasi dana desa mendorong terciptanya Kinerja Anggaran dalam pembangunan dan prioritas sesuai kesepakatan dengan masyarakat sesuaikan dengan visi misi dan tujuan pembangunan desa di Kabupaten Kepulauan Meranti dengan metode kuantitatif sebanyak responden 309 peserta. Hasil penelitian menunjukan masih perlunya Knowledge Mangement bagi anggota organisasi, Management Agile dalam menghadapi perubahan lingkungan dan urgensi keadaan saat ini, serta peningkatan pengetahuan dalam peraturan pelaksanaan anggaran dan ketrampilan bagi anggota untuk memotivasi stakeholder anggaran alokasi Dana Desa dalam peningkatan anggaran pada tahun mendatang.